The financial situation of students during the COVID-19 pandemic - Dennis H. Meier; Stephan L. Thomsen; Johannes Trunzer (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2022)
Many university students depend on employment during their studies. The closing of universities and the loss of many typical student jobs during the COVID-19 pandemic particularly affected their situation. Based on survey data from a major German university, we analyze changes in students' income and its composition throughout the different phases of the pandemic. Students' job income declined by 66% (total income by 19%), on average, during the first lockdown. There was a quick recovery during the reopening. Job income fell again in the second lockdown, but this decrease was only half as large as that in the first lockdown. Women and students from non-academic backgrounds were particularly affected by job income loss, which widened pre-existing financial inequalities. Students compensated for income losses by increasing loan financing and by reducing their leisure expenses. Although dropout intentions increased for all students, there are no differences across socio-economic groups thus far.
Keywords: I23; I24; 330; higher education; student earnings; student employment; inequality